Administration of NaHS Attenuates Footshock-Induced Pathologies and Emotional and Cognitive Dysfunction in Triple Transgenic Alzheimer’s Mice - Huang, Hei-Jen; Chen, Shu-Ling; Hsieh-Li, Hsiu Mei (Frontiers in Behavioral Neuroscience, 2015)
Alzheimer's disease (AD) is characterized by progressive cognitive decline and neuropsychiatric symptoms. Increasing evidence indicates that environmental risk factors in young adults may accelerate cognitive loss in AD and that hydrogen sulfide (H2S) may represent an innovative treatment to slow the progression of AD. Therefore, the aim of this study was to evaluate the effects of NaHS, an H2S donor, in a triple transgenic AD mouse model (3×Tg-AD) under footshock with situational reminders (SRs). Inescapable footshock with SRs induced anxiety and cognitive dysfunction as well as a decrease in the levels of plasma H2S and GSH and an increase in IL-6 levels in 3×Tg-AD mice. Under footshock with SR stimulus, amyloid deposition, tau protein hyperphosphorylation, and microgliosis were highly increased in the stress-responsive brain structures, including the hippocampus and amygdala, of the AD mice. Oxidative stress, inflammatory response, and β-site APP cleaving enzyme 1 (BACE1) levels were also increased, and the level of inactivated glycogen synthase kinase-3β (GSK3β) (pSer9) was decreased in the hippocampi of AD mice subjected to footshock with SRs. Furthermore, the numbers of cholinergic neurons in the medial septum/diagonal band of Broca (MS/DB) and noradrenergic neurons in the locus coeruleus (LC) were also decreased in the 3×Tg-AD mice under footshock with SRs. These biochemical hallmarks and pathological presentations were all alleviated by the semi-acute administration of NaHS in the AD mice. Together, these findings suggest that footshock with SRs induces the impairment of spatial cognition and emotion, which involve pathological changes in the peripheral and central systems, including the hippocampus, MS/DB, LC, and BLA, and that the administration of NaHS may be a candidate strategy to ameliorate the progression of neurodegeneration.